Transmiáion efficiency of Tunisian Potato leaf-roll virus isolates by Tunisian clones of the Nyzus persicae complex (Hemiptera: Aphididae) - Djilani Khouadja, F.=700 1 Rouze-Jouan, J.; Gauthier, J.P.; Bouhachem, S.; Marrakchi, M.; Fakhfakh, H.
(Es, En)
ilus., ref.
Keywords: APHIDOIDEA; INFECCION; INOCULACION; CLONES; PHYSALIS; VECTORES; TRANSMISION DE ENFERMEDADES; ESPAÑA; AISLADOS PLRV; AFIDOS; DAS-ELISA